1991
DOI: 10.1007/bf01297027
|View full text |Cite
|
Sign up to set email alerts
|

Towards a less costly but accurate test of gastric emptying and small bowel transit

Abstract: Our aim is to develop a less costly but accurate test of stomach emptying and small bowel transit by utilizing selected scintigraphic observations 1-6 hr after ingestion of a radiolabeled solid meal. These selected data were compared with more detailed analyses that require multiple scans and labor-intensive technical support. A logistic discriminant analysis was used to estimate the sensitivity and specificity of selected summaries of scintigraphic transit measurements. We studied 14 patients with motility di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(140 citation statements)
references
References 17 publications
1
137
0
2
Order By: Relevance
“…In 1991, from a study of 14 patients and 37 healthy subjects, it was reported that a limited number of data points, at 0, 2, and 4 h, provided an approximate and adequate representation of gastric emptying when compared with more frequent image acquisition (14). The same investigator group subsequently published a study on 35 patients using the simplified protocol and reported that more patients with delayed gastric emptying were detected at 4 h than at 2 h (3).…”
Section: Discussionmentioning
confidence: 95%
“…In 1991, from a study of 14 patients and 37 healthy subjects, it was reported that a limited number of data points, at 0, 2, and 4 h, provided an approximate and adequate representation of gastric emptying when compared with more frequent image acquisition (14). The same investigator group subsequently published a study on 35 patients using the simplified protocol and reported that more patients with delayed gastric emptying were detected at 4 h than at 2 h (3).…”
Section: Discussionmentioning
confidence: 95%
“…However, many centers use a cutoff of Ͼ70% emptied in the first hour as indicative of accelerated gastric emptying. Identifying accelerated gastric emptying may therefore require use of higher calorie meal (16) or nutrient liquids as the radiolabeled substrate. It is also worth noting that some patients may have delayed gastric emptying at 1 and 2 h, but normal emptying by 4 h. Such patients may benefit from prokinetic therapy.…”
Section: Gastric Emptying Scintigraphymentioning
confidence: 99%
“…Additionally, scintigraphic imaging involves radiation exposure, requires costly gamma camera equipment, and is time intensive for patients and medical personnel. A simplified imaging protocol to obtain images at 1, 2, and 4 h with a standard meal was first proposed at Mayo Clinic (16), and a variation using a commercial and standardized meal was subsequently validated in a large multinational study in 123 subjects (129). The standardized meal and study protocol have been recommended for adoption across institutions by a consensus statement from the American Neurogastroenterology and Motility Society and the Society of Nuclear Medicine (1).…”
Section: Gastric Emptying Scintigraphymentioning
confidence: 99%
“…It is important to define clinically the motor function of the stomach in order to understand the basis of the patients' symptoms and to develop appropriate therapeutic strategies (Camilleri et al, 1991). In 2000, Case et al emphasized that improvement of gastric emptying is on the top of the factors needed for achieving proper nutritional goals in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%